Рослини у святах календарного обрядового циклу Житомирського Полісся - Дмитренко, Алла; Dmytrenko, Alla (My University, 2013)
У статті на основі польових етнографічних матеріалів розглянуто роль рослин у календарно-обрядовому житті мешканців Ємільчинського й Новоград-Волинського районів Житомирської області. Відзначено, що в певні дні народного календаря різні трави й гілки дерев наділялися магічними властивостями. Наголошується, що багатою рослинною символікою наповнені здебільшого свята весняного й літнього календарних циклів.In the article, the role of plants is examined in calendar-ceremonial life of habitants of Emilchinsk and Novograd-Volynsk districts of the Zhitomir area on the basis of the field ethnographic materials. Marked, that different herbares and branches of trees were provided with magic properties in the certain days of folk calendar. It is marked that ceremonial actions spring and summer calendar cycles: to Greenery of holiday, Makoveya, Ivan Kupala, Spasa, Prechysta, Palm Sunday filled with a rich vegetable symbolics.
Plants Are in the Holidays of Calendar Ceremonial Cycle of Zhytomyr of Zhytomyr Polissya
Keywords: Полісся; Житомирщина; традиційно-побутова культура; календарні звичаї та обряди; рослини; культ рослин; культ предків; Polissya; Zhitomirschina; traditionally-domestic culture; calendar customs and ceremonies; plants; cult of plants; cult of ancestors